The Impact of Learning Skills on Academic Achievement and Learning Outcomes in High School - Asri; Asniwati; Irwan (Universitas Pendidikan Ganesha, 2024)
In obtaining student achievements and learning outcomes, students must have good skills and abilities. However, the fact is that many students still have low achievement and learning outcomes. This is urgent to research because there is a difference between theoretical expectations and reality to analyze learning skills and academic achievement within groups and to analyze differences in learning skills between male students and female students. The method in this research is quantitative by testing ANOVA. The subjects were 180 high school students. Data collection technique is using a learning skills instrument that contains two parts. The first section contains the demographics of the respondents. The second part also contains questions regarding learning skills. Instruments are assessed on a critical scale of 1 to 5 by distributing instruments using Google. A data analysis technique is using SPSS Version 25.0. Data analysis was analyzed using the Pearson correlation test to measure the relationship between learning skills and academic achievement. The results and findings show that the exam results show that there are no significant differences in learning skills among fourth-level students of different genders. ANOVA test results show that there are differences in learning skills among students in achieving academic achievement. The Pearson correlation test shows that there is a positive relationship between learning proficiency and academic achievement. The conclusion is that in obtaining achievements and learning outcomes, individual student learning skills and good academic performance are still needed.